Monitoring dan Evaluasi Kebijakan Program Bantuan Pangan Non Tunai (BPNT) Dalam Penanggulangan Kemiskinan di Kota Batu - Wiwit Wiwit; Tri Sulistyaningsih; Muhammad Kamil (Departemen Ilmu Pemerintahan Fisip Unhas, 2020)
This study aims to explain the problems in government programs in the provision of social assistance to the poor which are not appropriate. Based on the direction of President Joko Widodo through Ratas on March 16, 2016 states that social assistance is provided on a non-cash basis, one of which is through the BPNT program based on Permensos No.11 2018 which is a transformation of the Rastra program which has problems in distribution. The BPNT program is expected to reduce the burden of spending in meeting the basic needs of poor families, as social protection and poverty reduction. Batu City is one of the areas chosen as a Pilot Project since the BPNT program was formed in 2017. The implementation of the BPNT program in each region is not the same. There are even KPM who do not know if they receive BPNT Social assistance. So to find out the implementation of the BPNT program in Batu, monitoring and evaluation is needed in its implementation. The method in this study uses descriptive qualitative approach, providing an overview of developments in the application of the BPNT program in poverty alleviation. Data collection techniques are done by observation, interview and documentation. The research theory of the BPNT Program uses Monitoring and Evaluation of policies according to William Dunn who argues that monitoring is an internal and ongoing activity, a source of information which will later be used as an evaluation material to find out whether a policy is successful or not. The results of this study indicate that the implementation of monitoring and evaluation of the BPNT Program in Batu has implemented the principles of monitoring and evaluation and has been running quite well by BSP facilitators and the BPNT program is considered to have been on target, so as to accelerate the implementation of poverty reduction. BPNT program has been given to KPM Kota Batu as many as 5,649 KPM in 2018 then decreased in 2019 which is as many as 3,992 KPM. The inhibiting factors in monitoring and evaluating the BPNT program are first the capacity of Human Resources (HR) second, namely time.